Interactive multimedia for teaching nematology - Eisenback, J.D (Journal of nematology, 1993)
The availability of interactive multimedia authoring software programs promises to revolutionize the teaching of nematology. These programs integrate text, hypertext, graphics, animations, video, and sound. The user interacts with the information on demand in a nonlinear fashion. Beginning students can limit themselves to the general outlines of the subject, and advanced students can explore the information to the limits of their ability. Use of interactive multimedia does not eliminate the need for effective, enthusiastic teachers but provides a mechanism for the efficient transfer of information. An interactive multimedia presentation that supplements lectures in an introductory course is presented as an example of the application of this technology for teaching nematology